2018
DOI: 10.1101/363713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Disease Surveillance and Response (IDSR) in Malawi: Implementation Gaps and Challenges for Timely Alert

Abstract: Objective: The emerging and recent 2014 Ebola Virus Disease (EVD) outbreaks rang the bell to call upon efforts from globe to assist resource-constrained countries to strengthen public health surveillance system for early response. Malawi adopted the Integrated Disease Surveillance and Response (IDSR) strategy to develop its national surveillance system since 2002 and revised its guideline to fulfill the International Health Regulation (IHR) requirements in 2014. This study aimed to understand the state of IDSR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…In overall, we observed that average percentage timeliness tended to be lower compared to average percentage completeness in all the four performance groups. This observation is re ected in other similar studies [12], [32]. Nonetheless, as much as this observation was common among the four performance groups, the outlier performance group speci cally brings to light larger disparities between average completeness and timeliness.…”
Section: Discussionsupporting
confidence: 68%
“…In overall, we observed that average percentage timeliness tended to be lower compared to average percentage completeness in all the four performance groups. This observation is re ected in other similar studies [12], [32]. Nonetheless, as much as this observation was common among the four performance groups, the outlier performance group speci cally brings to light larger disparities between average completeness and timeliness.…”
Section: Discussionsupporting
confidence: 68%
“…In overall, we observed that average percentage timeliness tended to be lower compared to average percentage completeness in all the four performance groups. This observation is re ected in other similar studies [11], [29]. Nonetheless, as much as this observation was common among the four performance groups, the outlier performance group speci cally brings to light larger disparities between average completeness and timeliness.…”
Section: Discussionsupporting
confidence: 68%
“…For example, in Zambia some of the challenges found were inadequate trained staff, coordination challenges and poor infrastructure (13). Ghana and Malawi found some of the challenges to include lack of technical guidelines, lack of standard case definitions, inadequate supervision/feedback and low prioritization of surveillance activities by health workers (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Though varied, many challenges are similar across the countries that have evaluated and published their IDSR performance. These challenges include: inadequate financial resources, poor coordination, weak laboratory capacity, poor communication systems, poor supervision, erratic feedback, inadequate training of health workers, lack of IDSR technical guidelines and reporting tools (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%